The Twentieth Century - Strunk, Oliver 1901-1980; Morgan, Robert P. (New York Norton, 1997)
Twentieth-century music has been described as complex, vital, diverse, uncertain, experimental, self-conscious, innovative-the list is long and growing. Composers have been both credited with and accused of always searching for something "new," writing works that are mechanistic but romantic, meaningful but unskilled, beautiful but ugly! In The Twentieth Century, Robert P. Morgan helps us grasp the flavor of the era by presenting forty-five readings from the period, nearly all written by active participants in the musical developments of the time. Thus we tune in to the voices of some thirty composers-from Busoni to Babbitt, Ives to Xenakis, Satie to Stravinsky-and learn from performers Anderson and Landowska, philosopher-critics Adorno, Dahlhaus, and Meyer, and writers Cocteau, Barthes, and Eco.
Keywords: 20th Century (1901-2000); Music history